Wireless indoor tracking mobile entities - Wong, Zhi Ying. (2010)
Location information is an important contribution to many context-aware mobile applications both indoor and outdoor such as car navigation and logistics managements. There has been a rise of these applications in recent years due to the benefit and convenience it has brought to many people. Global Positioning System (GPS) was adopted to provide an accurate and efficient method for outdoor positioning. However, there is no specific technique could be used indoor. Indoor location determination is difficult due to the constant changing environment and the multipath fading effect. Researchers have developed many different techniques for it by using Bluetooth, Wireless Local Area Network (WLAN) and Global System for Mobile Communications (GSM). WLAN system is chosen for my research because it is provides large coverage and is widely available in many places now. WLAN techniques can be divided into two categories namely probabilistic and deterministic. A design for indoor location determination was created based on WLAN system. The design is a deterministic method. Unlike other methods which use complex models and calculations to improve accuracy of estimated location, the design created is simple and practical. It extracts important information required and reduces computation time by grouping locations into clusters. In addition, a classification technique was developed to handle APs with similar received signal strengths. A widget was created to test the effectiveness of the design on an emulator. The emulator works in the same way as mobile phones. The experiment will take place in two testbeds namely, pseudo map and Computer Lab located in school. The factors affecting the results, benefits and limitations of the design will be discussed. The results obtained from the implementation in real environment has showed that the program is able to obtain accurate location most of the time.